2014
DOI: 10.11648/j.jps.20140205.18
|View full text |Cite
|
Sign up to set email alerts
|

Plant Canopy, Tuber Yield and Growth Analysis of Potato under Moderate and Severe Drought Condition

Abstract: Abstract:Four CIP potato clones with 1 check variety Asterix were grown during 2010-11 and 2011-12 at Horticulture Research Farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh to observe the effect of water stress on canopy structure, yield and growth rate of potato. The study validated that all the genotypes showed reduction in plant height, number of above ground shoots per plant, tuber number per plant and yield by different degrees of drought. Significant yield reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The decrease in canopy diameter was significant under severe drought stress irrespective of the control ( F = 8.70; p < 0.05). This finding is in line with the work of Al-Mahmud et al [ 73 ]; which showed that canopy diameter was significantly decreased under severe drought stress in potato plants. These might be due to the traits they inherited, and they may determine the yielding potential of the crop.…”
Section: Resultssupporting
confidence: 93%
“…The decrease in canopy diameter was significant under severe drought stress irrespective of the control ( F = 8.70; p < 0.05). This finding is in line with the work of Al-Mahmud et al [ 73 ]; which showed that canopy diameter was significantly decreased under severe drought stress in potato plants. These might be due to the traits they inherited, and they may determine the yielding potential of the crop.…”
Section: Resultssupporting
confidence: 93%
“…According to Haverkort and Struik (2015) the number of sprouts that will develop depends on how many stems there will be produced per seed, and how many stems will survive and become tuber-bearing will depend on variety, seed tuber size, seed tuber health, physiological age, and environmental conditions. Vice versa, the number of above-ground organs per plant is mainly determined by the size of the tuber and its condition, and the pre-sprouting period also influences it (Al-Mahmud et al 2014). In this sense, farmers manipulate the average tuber size and tuber size distribution to reduce seed quality as a yieldlimiting factor.…”
Section: Resultsmentioning
confidence: 99%
“…Water deficit stress is one of the most important factors limiting the growth and yield of plants. To screen genotypes tolerant to drought stress in potatoes, from the distribution of assimilates and total live weight produced under stress conditions (Coleman, 2008), the ability to survive in severe water deficit stress conditions without losing leaves (Coleman, 2008), maximum leaf area index (Deshi et al, 2015), maximum leaf area index (Deshi et al, 2015), later leaf fall in dry conditions (Lahlou et al, 2003), maximum leaf area index and leaf durability period (Al-Mahmud et al, 2014), maximum the leaf surface index and its retention time (Deshi et al, 2015) and the highest relative water content and the chlorophyll index and the lowest electrolyte leakage rate (Nouri et al, 2015) are used. Water deficit stress is a common stress in potato production, leading to decreased tuber quality and yield.…”
mentioning
confidence: 99%